Analysis of the Role of Social Media in Business Centers in Kampoeng Batik Laweyan, Surakarta City - Putri, Febita Ayu Riswaning; Mustofa, Rochman Hadi (Dinasti Publisher, 2025)
This research aims to analyze the role of social media in developing business centers in Kampoeng Batik Laweyan, Surakarta. Social media is now a strategic tool in introducing products, building brands, and increasing interaction between business actors and consumers. In the context of Kampoeng Batik Laweyan, which is famous as one of the batik centers in Indonesia, the use of social media is considered important to expand the market and maintain the sustainability of batik traditions. The method used is a qualitative approach by interviewing batik business actors and analyzing social media content used in the center. The results of the study show that social media plays a major role in increasing the visibility of batik businesses, expanding market networks, and introducing the values ??and philosophy of Laweyan batik to domestic and foreign consumers. In addition, social media is also a means of interaction that allows direct suggestions and criticism from consumers, which also contributes to improving product and service quality. This study is expected to provide insight for other batik business actors in utilizing social media as an effective and sustainable marketing tool.